Village-Owned Enterprises and Rural Community Welfare: A Lesson from Malang of Indonesia - Agustina, Yuli; Winarno, Agung; Narmaditya, Bagus Shandy (Technium Social Sciences Journal, 2021)
The shifting paradigm from capital-based city to village development brings the potential to enhance community welfare. This paper aims to examine the enlargement of community well-being by optimizing village-owned enterprises (BUMDes) from management sides. This paper was conducted through several stages including, a survey to collect preliminary information, socialization, implementation, and evaluation. The activity was carried out in 13 villages located in Ngantang municipalities in Malang of Indonesia. The findings indicate that the problem experienced is the lack of knowledge of BUMDes management, which limits their obligations as village residents. The utilization of local potential has not been excavated and centered on BUMDes due to managers’ lack of human resource knowledge. The role of BUMDes in improving the local economy can be seen by maximizing existing efforts in the community to be associated with BUMDes. The one village one product, for example, the program can be supported with the existing BUMDes.